Decoding restorative justice: analysing the linguistic features of peace pacts - Balisong, Krizza Mae Chagyowen; Madrunio, Marilu Rañosa (Penerbit Universiti Kebangsaan Malaysia, 2025)
Peace pacts, locally called “bodong” or “pechen”, are written bilateral agreements defining inter-tribal relationships in the Cordillera Administrative Region, Philippines. Over the years, these peace pacts have gradually been codified by the Indigenous communities involved, thus producing Indigenous legal documents. This study focused on identifying the linguistic features of Indigenous legal documents, specifically the written peace pacts of Sadanga, Mountain Province, Philippines, on three levels: lexical, grammatical, cohesion and context. Through document analysis, results revealed that similar to state legal documents, Indigenous legal documents exhibit archaism, the use of legal jargon and collocations, repeated occurrences of synonyms, and the use of “whereas” clauses. However, unique features that accommodate the needs and context of the Indigenous communities involved were also observed. These include code-mixing, coinage, use of active voice and simple sentences, brevity, mixed perspectives, and use of cultural key terms. These results show that by combining legalese with local language and local writing practices, the Sadanga Indigenous community produces a hybrid legal document that not only reflects their culture and tradition but also upholds authority that governs inter-tribal relations, maintains peace, ensures proper use of resources, and resolves conflicts.